2016
DOI: 10.1111/ajt.13786
|View full text |Cite
|
Sign up to set email alerts
|

Use of the PD-1 Pathway Inhibitor Nivolumab in a Renal Transplant Patient With Malignancy

Abstract: Programmed cell death protein 1 (PD-1) is a receptor found on T cells, and when bound with its ligand PD-L1 or PD-L2, it negatively regulates T cells. Certain tumors, such as squamous non-small cell lung cancer and melanoma, evade T cell immune surveillance by upregulating PD-1 ligands. Blockade of PD-1 and its ligand can restore T cell-mediated tumor suppression (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 3 publications
1
60
0
1
Order By: Relevance
“…Although Lipson et al [51] had initially reported the successful administration of ipilimumab to 2 kidney transplantation patients with metastatic melanoma without any signs of rejection, they recently reported a case of tumor regression but allograft rejection after administration of pembrolizumab [52]. In addition, 3 cases of rejection were reported with the use of nivolumab in kidney transplant patients with melanoma [53,54,55]. Online supplementary Table 5 summarizes all 6 cases.…”
Section: Introductionmentioning
confidence: 99%
“…Although Lipson et al [51] had initially reported the successful administration of ipilimumab to 2 kidney transplantation patients with metastatic melanoma without any signs of rejection, they recently reported a case of tumor regression but allograft rejection after administration of pembrolizumab [52]. In addition, 3 cases of rejection were reported with the use of nivolumab in kidney transplant patients with melanoma [53,54,55]. Online supplementary Table 5 summarizes all 6 cases.…”
Section: Introductionmentioning
confidence: 99%
“…Several cases were reported of the administration of agents such as ipilimumab and nivolumab in liver or kidney transplant recipients [4–13]. No patients receiving ipilimumab developed graft rejection, whereas some of the patients receiving PD1 inhibitors presented with kidney and heart rejections and even graft loss [4, 6, 10, 14], indicating that these agents should be used with more caution in patients with vital organ transplantations (liver, heart).…”
Section: Discussionmentioning
confidence: 99%
“…However, the administration of agents that are explicitly designed to re-invigorate the T-cell response carries the clear risk of precipitating acute rejection, a lymphocytic infiltrative process, which could result in irreparable damage to the transplanted organ. Several cases have been reported of patients with kidney and liver transplants receiving checkpoint inhibitors, such as cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed-death 1 (PD-1) inhibitors, with increased risk of rejection appearing to be more frequent on anti-PD-1 therapy [4–13]. One patient was reported to receive anti-PD-1 therapy in the context of heart transplantation, developing an acute rejection [14].…”
Section: Introductionmentioning
confidence: 99%
“…The immune suppression regimen for both patients was reduced at least 6 weeks prior to the ipilimumab (Table 4) and the treatment was well-tolerated with partial response of the melanoma. However, more recently, two cases of acute rejection of kidney allograft after nivolumab treatment have been reported 49,50 as well as two additional cases of allograft rejections after a sequential administration of ipilimumab and nivolumab 51,52 . In all the above cases, regardless of rejection episodes, the patients’ immune suppression regimen was minimized prior to the initiation of immune checkpoint inhibitors.…”
Section: Checkpoint Inhibitors In Chronic Kidney Disease and Organ Trmentioning
confidence: 99%